2010
DOI: 10.1519/jsc.0b013e3181d82f8b
|View full text |Cite
|
Sign up to set email alerts
|

Six Weeks of High-Intensity Interval Training With and Without β-Alanine Supplementation for Improving Cardiovascular Fitness in Women

Abstract: The purpose of the present study was to evaluate the effects of cycle ergometry high-intensity interval training (HIIT) with and without beta-alanine supplementation on maximal oxygen consumption rate (VO2 peak), cycle ergometer workload at the ventilatory threshold (VT W), and body composition. Forty-four women (mean +/- SD age = 21.8 +/- 3.7 years; height = 166.5 +/- 6.6 cm; body mass (BM) = 65.9 +/- 10.8 kg; VO2 peak = 31.5 +/- 6.2 ml x kg(-1) x min(-1)) were randomly assigned to 1 of 3 groups: beta-alanine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 37 publications
5
67
0
3
Order By: Relevance
“…Previous research has also shown BA to be effective at increasing anaerobic thresholds measured by short bouts of intense exercise (Derave et al, 2007;Artioli et al, 2010). Despite previous reports of BA improving anaerobic thresholds, the effects on VT have been mixed with a few studies showing benefit Walter et al, 2010), while other studies have demonstrated no effect (Smith et al, 2009a(Smith et al, ,b, 2012Jordan et al, 2010), which is consistent with the current study. This may be a result of the graded exercise progression not dependent upon buffering capacity, as well as a result of using indirect calorimetry software to calculate VT, which has not shown to be highly reliable.…”
Section: P-valuesupporting
confidence: 86%
See 1 more Smart Citation
“…Previous research has also shown BA to be effective at increasing anaerobic thresholds measured by short bouts of intense exercise (Derave et al, 2007;Artioli et al, 2010). Despite previous reports of BA improving anaerobic thresholds, the effects on VT have been mixed with a few studies showing benefit Walter et al, 2010), while other studies have demonstrated no effect (Smith et al, 2009a(Smith et al, ,b, 2012Jordan et al, 2010), which is consistent with the current study. This may be a result of the graded exercise progression not dependent upon buffering capacity, as well as a result of using indirect calorimetry software to calculate VT, which has not shown to be highly reliable.…”
Section: P-valuesupporting
confidence: 86%
“…Previous studies have used various methods for quantifying a 'threshold' of fatigue to evaluate the effects of BA supplementation (Stout et al, 2006(Stout et al, , 2008Zoeller et al, 2007;McCormack et al, 2013), and the combination of BA + exercise (Kendrick et al, 2008;Smith et al, 2009a,b;Walter et al, 2010;Kern & Robinson, 2011). If BA can delay this threshold of fatigue, as demonstrated by McCormack et al, (2013), Stout et al, (2007)) and Stout et al, (2008), it may have functional outcomes in various clinical populations by improving the efficiency of activities of daily living and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…However, as a result of the greater concentration of carnosine than either bicarbonate or inorganic phosphate in the initial stages of muscle contraction, its buffering contribution may be quantitatively more important (Robergs et al 2004). In support, numerous studies have demonstrated the ergogenicity of b-alanine supplementation in anaerobic performance (Derave et al 2007;Hoffman et al 2007Hoffman et al , 2008Kendrick et al 2009;Stout et al 2007;Van Thienen et al 2009;Zoeller et al 2007), with less support in aerobic activities (Derave et al 2007;Kendrick et al 2008;Smith et al 2009;Stout et al 2007;Zoeller et al 2007) and only two previous studies evaluating the effects in women Walter et al 2010). The present results suggest a slight antioxidant potential, with a reduction in lipid peroxidation, which falls in line with the functional role related to the imidazole structure and further supports the role as a pH buffer.…”
Section: Discussionmentioning
confidence: 97%
“…All studies reported mean ages ranging from 18.4 to 85.3 and participants were overwhelmingly male. There were two studies which exclusively included female participants Walter et al, 2010), three studies that included 17-20 female subjects (Chung et al, 2012;Smith-Ryan et al, 2012;Stout et al, 2008) and another study which included one female participant (Baguet et al, 2010a). The participants ranged from elite level athletics to recreational level and the elderly.…”
Section: Characteristics Of Rctsmentioning
confidence: 99%